Measurement of nuclear pore complex contractility using FRET. - Neo, Sheng Xiong. (2012)
While the structure of the nuclear pore and the mechanisms underlying nuclear transport have been extensively studied, the contractibility of the nuclear pore during nuclear transport remains unanswered. Predecessors made use of electron microscopy for these studies but were met with much difficulties. In our study, we adopt a novel approach to investigate nuclear pore contractibility through Förster resonance energy transfer (FRET). By tagging various nucleoporins with fluorophores, FRET can be monitored between a pair of tagged nucleoporins. Combined with the solved conformation of the coat nucleoporins, the change in distance between a pair of tagged coat nucleoporins during nuclear transport can be investigated. Here, we report the successful cloning and tagging of a pair of coat nucleoporins, Nup107-EYFP and Nup133-ECFP. A channel nucleoporin, Nup62, and an adaptor nucleoporin, Nup93, were also successfully cloned and tagged with EYFP and ECFP respectively. However, only Nup62-EYFP and Nup93-ECFP localized correctly to the nuclear pore. They were selected for further studies, ultimately leading towards the aim of studying FRET between this pair of nucleoporins.